Optimization Rate Of Penetration In Directional Drilling With Adjustable Bit Rotating and Hydraulic Hole Cleaning - Herianto (European Journal of Applied Sciences, 2021)
Some directional well drilling has a penetration rate that is not optimal due to several things, including RPM and poor hole cleaning. RPM settings in directional drilling for build up and tangential sections are controlled by hydraulics on the downhole mud motor by adjusting flow rate and nozzle size in the hydraulic motor. The amount of mud that enters the nozzle inside the motor will provide optimum RPM. The amount of ROP is influenced by the pump rate and the power on the motor. To control good cleaning of the hole in the bit to clean the cutting at the bottom of the drill hole the BHHP/HHP value is at least 48%. Hole cleaning is based on turbulent flow properties, cutting concentration, cutting transport ratio, and particle bed index. The hole cleaning parameters in the annulus must consider the flow pattern that occurs and the parameters of good cutting. In this research, it will be studied in an integrated manner to regulate the pump rate and pressure by providing sufficient RPM in the downhole mud motor and cleaning the cutting at the bottom of the hole to prevent from occurring bit balling and regrinding from occurring.